SIMULACRA DAN RETORIKA DALAM SUSTAINABILITY REPORT: ADAKAH KONTRIBUSI PERAN AKUNTANSI? - Akhmad Riduwan; Andayani Andayani (Jurnal Riset Keuangan dan Akuntansi, 2020)
This study aims to evaluate the extent to which the accounting and sustainability report used by companies as a tool and rhetoric media to build a positive image and gain stakeholders legitimacy. The research is based on sustainability report content analysis from five public companies in Indonesia. Sustainability report content was confirmed by the socio-ecological activities that were actually carried out by the company around the reporting period. The results of the analysis are justified based on the concept of  simulacra from Jean Baurillard, a French philosopher. The results showed that 98.43 percent of positive sustainability issues were disclosed in the sustainability report, but for negative issues, only 12.5 percent were disclosed. In the perspective of Jean Baudrillard's thinking, sustainability report contains four levels of simulacra, in which management accounting has a role in the process of creating simulacra and the development  of rhetoric.Keywords: accounting, sustainability report, simulacra, rhetoric, Jean Baudrillard.